PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA BANK MUAMALAT CABANG DEWI SARTIKA DI JAKARTA TIMUR - Rifqi, Muhammad; Kumara, Dedek (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of service quality and product quality on customer satisfaction at the Bank Muamalat Dewi Sartika branch in East Jakarta. This research uses quantitative methods. The population in this study was 2297 and the total sample of respondents was 96. The sampling technique used simple random sampling. The results of the research show that partially service quality (X1) has an effect on customer satisfaction. The regression equation value Y = 12.454+0.437X1+0.276X2, the correlation coefficient value on R Square is 0.425, meaning that the service quality (X1) and product quality (X2) variables have an effect. on customer satisfaction (Y) was 42.5% while the remaining 57.5% was influenced by other factors not examined in this research. The service quality variable obtains a calculated t value > t table or (6.892 > 1.985) while the product quality variable obtains a calculated t value > t table or (6.654 > 1.985). Thus, Ho3 is rejected and Ha3 is accepted. Simultaneously, service quality and product quality have a positive and significant effect on customer satisfaction with a significant value so that the value of fcount = 34.309 > ftable = 3.090. From these results it can be concluded that both service quality and product quality together have a significant and simultaneous effect on customer satisfaction.